2019
DOI: 10.1088/1742-6596/1218/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Literacy of Male and Female Students in Solving PISA Problem by “Shape and Space” Content

Abstract: This is a descriptive research which aims to describe mathematical literacy of male and female students by solving PISA problem. Mathematical problems are not only related to calculations, but how our ability to apply mathematical knowledge to solve problems in daily life. The importance of mathematical literacy can be seen from the PISA. The content of this research is shape and space content. Determination of this mathematical level is corresponding by some indicators which has been developed. It has three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Untuk konten space and shape, hasil kajian (Nasution et al, 2019) masalah yang baik. Penelitian lain juga menunjukkan hasil yang sama yaitu bahwa kemampuan peserta didik dalam menyelesaikan masalah konten ini, hanya berada pada kategori rendah dan sedang (Trapsilasiwi et al, 2019). Lebih lanjut menurut (Efriani et al, 2019), dalam menyelesaikan masalah konten ini kemampuan yang banyak nampak adalah penalaran dan representasi matematis, sedangkan kemampuan yang rendah adalah komunikasi matematis, yaitu lemahnya peserta didik dalam menjelaskan jawaban secara terperinci.…”
Section: Analisis Kemampuan Matematika Peserta Didikunclassified
“…Untuk konten space and shape, hasil kajian (Nasution et al, 2019) masalah yang baik. Penelitian lain juga menunjukkan hasil yang sama yaitu bahwa kemampuan peserta didik dalam menyelesaikan masalah konten ini, hanya berada pada kategori rendah dan sedang (Trapsilasiwi et al, 2019). Lebih lanjut menurut (Efriani et al, 2019), dalam menyelesaikan masalah konten ini kemampuan yang banyak nampak adalah penalaran dan representasi matematis, sedangkan kemampuan yang rendah adalah komunikasi matematis, yaitu lemahnya peserta didik dalam menjelaskan jawaban secara terperinci.…”
Section: Analisis Kemampuan Matematika Peserta Didikunclassified
“…Shape and space are content that includes phenomena about the visual world that entail patterns, characteristics of objects, locations, and orientations, representations of objects, encoding visual information, navigation, and dynamic interactions connected to natural forms (OECD, 2019). The research conducted by Trapsilasiwi (2019) found that Indonesian students' ability to solve mathematical literacy problems on shape and space is still in the low to medium range. This study uses mathematical literacy problems with the shape and space content to describe students' arguments in the problem-solving process because shape and space content not only makes up one of the PISA contents but also contains elements of curriculum-based mathematics.…”
Section: Introductionmentioning
confidence: 99%